Pelatihan Dasar Instalasi Listrik Di Pondok Pesantren Markaz Hadist Bilal Bin Rabbah - Sekarsari, Kartika; Rizal, Syaiful; Rozak, Ojak Abdul (CV. ITTC INDONESIA, 2024)
Basic electrical installation training prepares participants with the knowledge and skills to install, maintain, and repair electrical systems safely and efficiently. The training, which is packaged in community service activities (PKM) at the Markaz Hadist Bilal bin Rabah Islamic Boarding School in Tangerang Regency, aims to provide practical knowledge and skills for students so that they not only have religious knowledge but also technical skills in electrical matters that can be useful for them, at least for themselves and their immediate environment.However, in the future, if they have sufficient skills supported by a license or certification from a professional certification body related to the electrical sector. In this case, they can utilize these skills to carry out electrical installation work legally and safely in commercial and public contexts. The results achieved in this activity were that the students could participate in basic electrical installation training activities well, and most of the students were satisfied with the training they received and showed enthusiasm for further learning in the field of electricity.